Systematic Literature Review: Students' Conceptual Understanding Through Discovery Learning Assisted by GeoGebra - Ghefira Tasfiah Zahra; Eyus Sudihartinih (Universal Education, 2025)
This study aims to systematically examine the effectiveness of the Discovery Learning model assisted by GeoGebra in enhancing students’ mathematical conceptual understanding. Using the Systematic Literature Review (SLR) method based on PRISMA guidelines, twelve relevant national articles published between 2021 and 2024 were analyzed. The findings indicate that integrating GeoGebra into Discovery Learning has a positive impact by promoting interactive and exploratory learning experiences. Improvements are reflected in students’ learning outcomes and active engagement in the learning process. However, existing research is still limited to specific topics. Therefore, further development is needed, including the use of GeoGebra Class and interactive teaching materials that students can access independently.